VESICO-DUODENAL FISTULAS AND OBSTRUCTIVE SMALL BOWEL OBSTRUCTION IN CHOLELITHIASIS - Подолужный, Валерий Иванович; Пельц, Владислав Александрович; Радионов, Игорь Александрович; Павленко, Владимир Вячеславович; Старцев, Андрей Борисович (Medicine in Kuzbass, 2021)
Aim – Evaluation of the incidence of pressure ulcers and vesicoduodenal fistulas in cholcystolithiasis, as well as the incidence and effectiveness of basic diagnostic studies of gallstone obstructive small bowel obstruction.Materials and methods. Over the past 10 years, we have analyzed 5055 cholecystectomies in the surgical department N 2 of the Kuzbass Clinical Emergency Hospital named after M.A. Podgorbunsky. And for the period from 1997 to 2021 analyzed the surgical treatment of 1102 patients with acute mechanical intestinal obstruction in the surgical department N 1 of the Kuzbass Clinical Hospital of Emergency Medical Care named after M.A. Podgorbunsky.Results. At 5055 cholecystectomies, 10 (0.19 %) cases of biliodigestive fistulas were encountered, including 4 (0.08 %) vesico-duodenal and 6 (0.12 %) vesico-colonic fistulas. Cholecystectomy was combined with bowel suturing. In 1102 patients urgently operated on with mechanical intestinal obstruction, gallstone ileus was detected in 5 patients (0.45 %). Convincing indications for surgical treatment were vomiting and expansion of the initial sections of the small intestine when it was contrasted with a delay in the advance of barium suspension. They were limited in elderly patients to enterotomy and lithoextraction.Conclusion. In 0.08 % of cases, with long-term cholecystolithiasis, vesico-duodenal fistulas are formed. Obstructive gallstone small bowel obstruction occurs in 0.45 % of those operated on with mechanical intestinal obstruction. Diagnostic difficulties when using radiation methods of examination do not arise.
Keywords: gallstone disease; acute intestinal obstruction; biliodigestive fistulas; surgical treatment; radiation diagnostics